Relações étnico-raciais e rendimento escolar : a criança negra na alfabetização - Costa, Eliete Gonçalina dos Santos (2018)
This master's research aimed to analyze the implications of racial discrimination in the school performance of black children in classes of the 2nd and 3rd years of Elementary School of the Municipal School of Basic Education Mário Antunes de Almeida, located in the municipality of Várzea-Grande-MT. Researches indicate that in Brazilian society racial inequalities tend to disadvantage black students, which denounces the existence, in the educational context, of a discrepancy in the learning process among students, tied to racial characteristics. Starting from the question: Can racial discrimination in the school educational space affect the performance of black children in literacy? We also try to answer the following questions: How does racial discrimination fit into the school space? How does it imply in the black child's school performance? What is this child's understanding of racial discrimination? This led us to define as the object of investigation the school performance of black children in the literacy phase. Thus, we articulate the research in three parts, the first one consisting of the theoretical approach based on productions on racial relations in Brazilian society, whose main axes were: black population in Brazil, schooling of black population and black child in school space. The second part refers to the methodological conceptions that underpinned the research. We chose the qualitative approach that, according to Ribeiro (2015), its central objective is the understanding of the reality lived by those involved and its intention to understand the complexity of a particular reality investigated, its meanings and its relation with the wider social context . We chose the oral history method and the technique of the instruments for data collection constituted of participant observation and semi-structured interview. We counted on 14 participants, being 5 teachers and 9 students. The third part was devoted to the analysis of the data collected during field research, which enabled us to articulate the theoretical and methodological foundations for an analytical discussion of the different situations related to going to the field. It is possible to observe that the black child is still submerged in the cultural, social end economic determinations that are already preestablished in the school, which are seen as natural by much of the school community